Comparison of Management of Developmental Dysplasia of the Hip in a Pavlik Harness by Orthopaedic Surgeons, Orthopaedic Pediatricians, and Advanced Practice Providers. Issue 3 (July 2019) - Bellevue, Kate D.; Bompadre, Viviana; Lindberg, Antoinette W.
Abstract : Developmental dysplasia of the hip (DDH) is common, with high success rates of treatment in a Pavlik harness for children less than 6 months old. We performed a retrospective review, analyzing the outcomes of patients with DDH managed in a Pavlik harness by orthopaedic surgeons, an orthopaedic-trained physician, and advanced practice providers (APPs). There was no significant difference among provider types in patients requiring operative procedures of any kind. A straightforward treatment of DDH can be performed by orthopaedic-trained pediatricians and APPs, with referral to an orthopaedic surgeon if the patient fails treatment in a Pavlik harness.